2022
DOI: 10.4236/wjcd.2022.127041
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Clinical and Angiographic Characteristics in Acute Coronary Syndrome Patients in Dakar, Senegal

Abstract: Background: Coronary artery disease (CAD) is in relentless progression, along with the adoption of western lifestyle in sub-Saharan Africa. In Senegal, the incidence of acute coronary syndrome (ACS) rose from 5% to 12% in Dakar during the last 20 years. That increase was observed in both women and men, and according to current data, the former paid the heaviest price in terms of mortality compared to men. In this study, we aim to retrospectively assess the clinical characteristics and angiographic profile of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…A retrospective analysis of the angiographic pro le of ACS patients in two tertiary care centers in Dakar, Senegal, described single vessel disease as the most common, followed by triple vessel disease. 25 In-hospital outcomes study, the in-hospital mortality was 1.3%, with a higher incidence (6.6%) of periprocedural death in emergency cases than in elective cases (0.3%). Based on a systematic review of ACS in sub-Saharan Africa, in-hospital mortality was found to be variable, ranging from 1.2-24.5%, and primarily in uenced by the study populations and revascularization procedures performed.…”
Section: Ethnicitymentioning
confidence: 95%
“…A retrospective analysis of the angiographic pro le of ACS patients in two tertiary care centers in Dakar, Senegal, described single vessel disease as the most common, followed by triple vessel disease. 25 In-hospital outcomes study, the in-hospital mortality was 1.3%, with a higher incidence (6.6%) of periprocedural death in emergency cases than in elective cases (0.3%). Based on a systematic review of ACS in sub-Saharan Africa, in-hospital mortality was found to be variable, ranging from 1.2-24.5%, and primarily in uenced by the study populations and revascularization procedures performed.…”
Section: Ethnicitymentioning
confidence: 95%